The tainted khan - Matharu, Taran (Matharu, Taran. Soulbound saga, 2025)
"The next installment in New York Times bestselling author Taran Matharu's Soulbound Saga, continuing the harrowing journey of Jai as he navigates returning to his own people, growing in his magic and as a warrior, fending off attacks both without and within...and, of course, bonding even more with his dragon!"--